ÉVALUER LES CONNAISSANCES IMPLICITES ET EXPLICITES EN FRANÇAIS LANGUE ÉTRANGÈRE PAR LES TESTS DE JUGEMENT DE GRAMMATICALITÉ : ANALYSE DES OUTILS ET PRÉSENTATION DES RÉSULTATS DE LA RECHERCHE - Piegzik, Wioletta A. (Neofilolog, 2020)
The aim of this paper is to evaluate implicit and explicit knowledge among Polish speaking students studying French as a foreign language in the academic environment. In the first part, we discuss a timed grammaticality judgment test (TGJT) as an instrument for measuring implicit knowledge and an untimed grammaticality judgment test (UGJT) as a tool for evaluating explicit knowledge and we propose solutions to sidestep some of the weaknesses of both these instruments which were observed in our research. The second part focuses on the presentation of the research results, leading to the conclusion that the group of students at A2 level develop implicit and explicit knowledge in a fairly balanced way